2014
DOI: 10.3354/esr00580
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and diversity of two highly vulnerable carcharhinids in Australian waters

Abstract: Molecular techniques were employed to investigate genetic structure and diversity in dusky Carcharhinus obscurus and sandbar C. plumbeus sharks in the Indo-Australian region. Tissue samples of 423 C. obscurus and 442 C. plumbeus defined 18 and 11 mtDNA ND4 haplotypes, respectively. For C. obscurus, weak genetic differentiation was detected be tween eastern and western Australian waters (pairwise Φ ST = 0.04437, p < 0.008; pairwise F ST = 0.02403, p < 0.035), suggesting the delineation of 2 independent populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…Our findings showing dusky shark movements within, but not between the southwest and east coasts support the separated population structure suggested by Geraghty et al (2014), with two separated populations in the east and west coasts. These findings challenge the hypothesis of panmixia within Australia proposed by other genetic studies (Ovenden et al, 2009;Benavides et al, 2011a;Junge et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings showing dusky shark movements within, but not between the southwest and east coasts support the separated population structure suggested by Geraghty et al (2014), with two separated populations in the east and west coasts. These findings challenge the hypothesis of panmixia within Australia proposed by other genetic studies (Ovenden et al, 2009;Benavides et al, 2011a;Junge et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…Genetic studies have suggested large-scale stock segregation of bronze whalers between Australia-New Zealand, South Africa-Namibia, and Peru (Benavides et al, 2011b), and some delineation within Australia between WA and the rest of the Australian population (Junge et al, 2019). Dusky sharks are currently considered to have an eastern and western stock in Australia, with conventional and electronic tracking showing that dusky sharks move between SA and WA (Rogers et al, 2013b), and genetic analyses suggesting restricted gene flow between eastern and western Australia (Geraghty et al, 2014). However, previous and recent genetic analyses have also proposed panmixia within Australia (Ovenden et al, 2009;Benavides et al, 2011a;Junge et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…), dusky (Geraghty et al . ) and scalloped hammerhead sharks (Daly‐Engel et al . ), but not blue sharks (Ovenden et al .…”
Section: Discussionmentioning
confidence: 99%
“…() and Geraghty, Williamson et al. () estimated overall observer accuracy of OTLF observers during 2008, 2009 and 2010 to be very high for sharks identified at sea as sandbar (~99%, n = 487 sharks), spinner (~98%, n = 190) or dusky (~97%, n = 296) shark. Similarly, observer accuracy for blacktip sharks and scalloped hammerhead during those years was 96% ( n = 100) and ~91% ( n = 46), respectively (W. G. Macbeth, unpublished data).…”
Section: Methodsmentioning
confidence: 99%